“Kematian” Kapan Waktunya Umat Beriman Dikatakan Bangkit Dari Kematian? (Suatu Tinjauan Eskatologis) - Klau, Yohana Aek (JURNAL PROPHETA, 2021)
This article is specifically about “the death and resurrection of the dead” which is a point of the great theme of Christian eschatology and existence. The author focused moreattention on the issue of death and resurrection of the dead. Death is often seen as amystery. The world of the dead is logically a world full of question marks. Even thoughwe know death is a certainty, our reason is still groping, what is really behind death.Certainty that behind death there is life, even happiness we can get if we look at itthrough the lens of faith.Through the suffering, death and resurrection of Jesus we obtain forgiveness ofsins and salvation. In His resurrection Jesus obtained for us a resurrection with Him.Christ has been raised from the dead as the firstborn of those who have died. For just asdeath came because of one man, and so, the resurrection of the dead came because of oneman. Jesus rose as He is the Christ. Thus we will rise with Him with our body and soul.With the resurrection of Jesus, our mortal life will someday share in the glory of Jesus'life.